DIAGNOSTIC METHODS FOR NON-ALCOHOLIC FATTY LIVER DISEASES ALTERNATIVE TO LIVER BIOPSY: A REVIEW - Bodakhe, Surendra H; Gupta, Sanjay Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Non-alcoholic fatty liver diseases (NAFLD) are the most occurring chronic liver diseases caused by hepatic manifestation of metabolic syndromes like insulin resistance in Type-2 diabetes, obesity and hyperlipidemic condition. Indian men have a high prevalence of NAFLD. Genetic factor is also an important consideration for NAFLD. The core aim of this study is to focus on non-invasive biochemical markers for diagnosis of NAFLD as an alternative to liver biopsy. Biopsy is the gold standard for NAFLD; however a variety of studies powerfully suggest that due to the limitation and risk of biopsy, as well as improvement of the diagnostic accuracy of biochemical markers, biopsy should no longer be considered obligatory. Thus, due to the limitation of liver biopsy, numerous biomarkers has been developed recently, which may provide more accurate results than an inferior quality liver biopsy. Some important biomarkers are caspase-cleaved cytokeratin-18, breath biomarker, circulating microRNAs, abdominal ultrasound, adipocytokines, etc. Keywords: Adipocytokines, Cytokeratin-18, Liver biopsy, MicroRNAs, Non-alcoholic fatty liver diseases, Non-invasive biomarkers Â 